Detection of Subpubic Tumor Causing Bladder Outlet Obstruction by 3D Perineal Ultrasound - Albrich, S.; Steetskamp, J.; Rommens, K.; Porta, S.; Battista, M.; Hoffmann, G.; Skala, C. (Geburtshilfe und Frauenheilkunde, 2015)
This case report shows that 3D perineal ultrasound can be superior to clinical examination and routine 2D perineal ultrasound in the detection of an unusual subpubic tumor. A 73-year-old female patient was referred to our urogynecological outpatient unit complaining of over-active bladder symptoms and voiding dysfunction for 3 years. Gynecological examination found no signs of pelvic organ prolapse or abnormality in the vaginal cavity. Routine 2D perineal ultrasound showed substantial residual urine (ca. 300 ml on catheter) and limited bladder neck mobility, but no signs of pelvic organ prolapse. Use of standardized 3D perineal ultrasound revealed a 24 × 26 × 32 mm spherical, hypoechoic tumor below the pubic symphysis between the distal urethra and the pubic bones. This structure was mistaken for the pubic symphysis in the midline on 2D ultrasound performed earlier. At surgery, the tumor was completely excised through a vaginal incision between the urethra and the pubic symphysis. After an uneventful postoperative recovery the patient developed de-novo stress urinary incontinence, which was corrected successfully by the insertion of a retropubic tension-free suburethral sling after an interval of 8 weeks. After a further follow-up of 8 weeks the patient reported well-being, urinary continence and no voiding dysfunction; no abnormalities were found on examination. In conclusion, 3D perineal ultrasound is a useful additional tool for the diagnostic workup of bladder outlet obstruction.
Keywords: sonography; dysuria; urinary incontinence; benign vaginal tumor; gynecology